Anti Ulcer Activity of Methanolic and Aqueous Extracts of leaves of Gymnema sylverstre in Rats - kumar, Shankul (International Journal of Pharmaceutical & Biological Archive, 2012)
Anti Ulcer Activity of Methanolic and Aqueous Extracts of leaves of Gymnema sylverstre in Rats